Investigating effects of histone tail modification on chromatin compaction in nucleosome arrays - Abdollah Allahverdi (2011)
All eukaryotic organisms have elaborated ways of packaging DNA into chromosomes. Genetic processes, both vital such as transcription and replication and pathological such as cancer and viral infection depend on DNA in the context of chromatin. Chromatin consists of a linear array of uniform units called nucleosomes. The nucleosomes are made of DNA which carries a high negative charge and highly conserved and basic proteins, the histones. Unstructured N-termini of the histones called “histone tails” are believed to mediate inter-nucleosomal interactions leading to condensed chromatin. Histone tails are subject to a range of post-translational modifications, the most common of which, acetylation of the lysine ε-amino group, neutralizes the positive charge will induce decondensation of chromatin. A detailed characterization of the molecular interactions of histone tail mediated NCP interactions is of relevance for understanding the physical mechanisms underlying the epigenetic control of gene regulation.